Ubud: From The Origins to 19201 - Jean Couteau (Pusat Kajian Bali Universitas Udayana, 2013)
AbstractToday’s historis often tries to weave together unquestionablefacts with a narrative that consciously gives room to pastmyths and legends. The following article about the famous“cultural” resort of Ubud freely applies this approach to history.Myths and legends about the origin of Ubud combine withunquestionable historical facts to convey, beyond the Ubud’sraw history proper, the prevailing athmosphere of Ubud’spre-modern past. Thus the mythical seer Resi Merkandayais made to appear alongside the story of the kembar buncing(fraternal, non-identical twins) of the House of Ubud, and thehistory of Western presence and intervention.